Novel homozygous variant of carbonic anhydrase 8 gene expanding the phenotype of cerebellar ataxia, mental retardation, and disequilibrium syndrome subtype 3. Issue 11 (18th August 2020) - Paternoster, Lionel; Soblet, Julie; Aeby, Alec; De Tiège, Xavier; Goldman, Serge; Yue, Wyatt W.; Coppens, Sandra; Smits, Guillaume; Vilain, Catheline; Deconinck, Nicolas
Abstract: We report the case of an 11‐year‐old Syrian girl born to consanguineous parents, who presents an ataxic gait from early childhood. On clinical examination, she presented a severe static ‐ kinetic cerebellar syndrome, walking without support is possible for short distances only. Strikingly, three consecutive MRIs did not show any sign of cerebellar abnormalities, but a brain positron emission tomography (PET) using [18F]‐fluorodeoxyglucose (FDG) demonstrated a clear decrease in glucose metabolism in the cerebellum as well as the anterior and medial temporal lobe bilaterally. A clinical exome analysis identified a novel homozygous c.251A > G (p.Asn84Ser) likely pathogenic variant in the carbonic anhydrase 8 (CA8) gene. CA8 mutations cause cerebellar ataxia, mental retardation, and disequilibrium syndrome subtype 3 (CAMRQ3), a rare genetically autosomal recessive disorder, only described in four families, so far with the frequent observation of quadrupedal gait. The proband differed with other reported CA8 mutations by the absence of clear cerebellar signs on brain MRI and the presence of focal seizures. This report expands the clinical spectrum associated with mutations in CA8 and illustrates the possible discrepancy between (mild) neuro‐radiological images (MRI) and (severe) clinical phenotype in young individuals. In contrast, the observation of clear cerebellar abnormal metabolic findings suggests that the FDG‐PET scan may be used as an early marker for hereditary ataxia.